NITROGÊNIO E SISTEMAS DE CULTIVO NA EXPRESSÃO DOS COMPONENTES DE PRODUÇÃO DO TRIGO - Mattioni, Tânia C.; Matter, Edegar; Antonow, Diovane; Arenhardt, Emilio G.; Schiavo, Jordana; Fontaniva, Cristiano; Gaviraghi, Juliano; Krüger, Cleusa A. M. B.; Silva, Jose A. G. d.; Oliveira, Juliana M. d. (Salão do Conhecimento, 2013)
Resumo